Individual care plans can reduce hospital admission rate for patients who frequently attend the emergency department. Issue 8 (1st June 2010) - Newton, Alastair; Sarker, Shah Jalal; Parfitt, Andy; Henderson, Katherine; Jaye, Peter; Drake, Nicola
Abstract : Aim: To investigate the impact, in terms of hospital admission and investigations, of individual care plans for patients who frequently attend the emergency department (ED). Method: 32 patients who regularly attended the ED at St Thomas' Hospital were included in the study. After review of ED and hospital case records, an individual care plan was prepared for future attendances. The numbers of ED attendances, hospital admissions and investigations were collated from the electronic patient record system and compared for the 12 months prior to and 12 months after introduction of the care plan. Primary outcome measure was reduction in the number of hospital admissions (as a percentage of ED attendance). Secondary outcome measures were a reduction in the number of investigations and ED attendances. Results: In the 12 months prior to introduction of the individual care plans, the 32 patients accounted for 858 ED attendances and 209 admissions to hospital. In 12 months after introduction of the care plans, the number of ED attendances fell to 517, with only 77 hospital admissions. Median number of hospital admissions (as a percentage of ED attendances) fell from 18.8% to 7.1% (p=0.014) after introduction of the care plan. There were also reductions in median number of ED attendances (19 vs 5, p=0.001), median number of radiology tests (4 vs 1, p=0.001) and median number of blood tests (55 vs 12, p<0.001). Conclusions: Individual care plans for a carefully selected group of patients who frequently attend the emergency department can result in a decrease in the number of hospital admissions and number of investigations.